Comprehensive evaluation of window-integrated semi-transparent PV for building daylight performance. (January 2020) - Liu, Dingming; Sun, Yanyi; Wilson, Robin; Wu, Yupeng
Abstract: Building-integrated semi-transparent photovoltaic windows (PV windows) have been considered as a potential candidate to replace conventional windows to improve building energy efficiency and hence reduce carbon emissions. With the integration of PV windows, the indoor luminous environment may be significantly affected. The presence of solar cells may cause undesirable shading, low illuminance levels and affect colour quality of the transmitted daylight. Therefore, it is important to comprehensively assess daylight performance of PV windows to ensure a comfortable luminous environment. In this study, the daylight performance of Cadmium telluride (CdTe) PV window with four different transparencies (i.e. 20%, 30%, 40% and 50%) applied to a cellular office space has been assessed in terms of daylight quantity and daylight quality. RADIANCE was selected to predict the annual daylight performance through advanced dynamic metrics including Useful Daylight Illuminance (UDI), simplified Daylight Glare Probability (DGPs) and Illuminance Uniformity (Uo). Correlated Colour Temperature (CCT) and Colour Rendering Index (CRI), which are two attributes to characterise the colour quality of transmitted daylight were used to evaluate performance of the selected PV windows. CCT and CRI were calculated under three CIE standard daylight scenarios (CCT of 4000 K, 6500 K and 25000 K respectively). It is found that CdTe PV windows can significantly improve the homogeneity of daylight distribution on a task area located close to the window and reduce the risk of daylight glare when compared with the performance of a conventional double glazing. Moreover, the recommended CCT (i.e. 3000–7500 K) can be achieved with the employment of CdTe PV windows under 4000 K and 6500 K daylight scenarios. All of the CdTe PV windows examined were able to maintain CRI at a comfortable level i.e. above 90 under the three daylight scenarios. Highlights: To evaluate the indoor luminous environment with semi-transparent CdTe window installed. To assess the UDI, DGPs and UO using RADIANCE with CdTe windows installed. To evaluate CCT and CRI influenced by CdTe windows using CIE standard. The semi-transparent CdTe window offers good daylight quality and quantity.